2005
DOI: 10.1002/pola.20811
|View full text |Cite
|
Sign up to set email alerts
|

Structural defects in poly(vinyl chloride)

Abstract: This article describes, in narrative style, the research of the author and his associates, performed over a period of 30 years, that led to the identification and quantification of the anomalous structures in poly(vinyl chloride) (PVC) and to detailed descriptions of their mechanisms of formation. Also examined here are the implications of this work for the thermal stability of PVC, for the overall chemical mechanism of vinyl chloride polymerization, and for other relevant aspects of the chemistry and technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 59 publications
2
86
0
Order By: Relevance
“…The mechanisms involved in the formation of the structural defects during the free radical polymerization of VCM were extensively studied over the last decades. 15,16 On the other hand, due to the absence of side reactions, in the LRP approach the molecular weight is completely controlled by the ratio monomer/initiator. Previous experiences had shown that in the range of 21-428C, the polymer is free of structural defects.…”
Section: Thermoanalytical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms involved in the formation of the structural defects during the free radical polymerization of VCM were extensively studied over the last decades. 15,16 On the other hand, due to the absence of side reactions, in the LRP approach the molecular weight is completely controlled by the ratio monomer/initiator. Previous experiences had shown that in the range of 21-428C, the polymer is free of structural defects.…”
Section: Thermoanalytical Resultsmentioning
confidence: 99%
“…13,14 Because of its technological relevance and scientific importance, the thermal degradation and stabilization mechanism of PVC has been the subject of various studies and reviews. 15,16 The internal allylic chloride and tertiary chloride structural defects that are formed during the polymerization are identified as being structures responsible for the beginning of the dehydrochlorination process. Despite the low concentration in the PVC chains (allyl chloride concentration of 0.9 per molecule 17 ), the structural defects are responsible for the thermal dehydrochlorination process.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Instead of further propagation after the Cl-shift, the chlorine attached to the third carbon atom can be abstracted by a monomer unit, producing an 1-chloro-2-alkene end group (EA, end allylic structure). [9] The eliminated chlorine radical initiates a new polymer chain that differs from other chains by the typical 1,2-dichloroalkane end group. This reaction is also referred to as chain transfer to monomer, and it is of great practical importance, as already mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…These ÀCH 2 Cl branches are the most frequent short chain branches in PVC (approximately 4/1000 VC units), as is shown by 1 H and 13 C NMR measurements. [8][9][10][11] It is accepted that this well-known type of defect structure is mainly introduced in the chain by the mechanism described above. [9,12] The methyl branch is not thermally unstable since there are no chlorine atoms bonded to the tertiary carbon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation